2010
DOI: 10.1371/journal.pone.0009498
|View full text |Cite
|
Sign up to set email alerts
|

Increased Health Risk in Subjects with High Self-Reported Seasonality

Abstract: BackgroundSeasonal variations in mood and behaviour, termed seasonality, are commonly reported in the general population. As a part of a large cross-sectional health survey in Hordaland, Norway, we investigated the relationship between seasonality, objective health measurements and health behaviours.Methodology/Principal FindingsA total of 11,545 subjects between 40–44 years old participated, completing the Global Seasonality Score, measuring seasonality. Waist/hip circumference, BMI and blood pressure were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…The SPAQ has been demonstrated to be reliable in that it measures consistently and to be valid in that it measures what it was designed to measure [ 49 , 51 53 ]. However, it has been criticized for having low specificity, meaning that results may suggest people who do not have SAD will score as though they do [ 48 ].…”
Section: An Explanation Of Seasonal Affective Disorder (Sad)mentioning
confidence: 99%
“…The SPAQ has been demonstrated to be reliable in that it measures consistently and to be valid in that it measures what it was designed to measure [ 49 , 51 53 ]. However, it has been criticized for having low specificity, meaning that results may suggest people who do not have SAD will score as though they do [ 48 ].…”
Section: An Explanation Of Seasonal Affective Disorder (Sad)mentioning
confidence: 99%
“…General anxiety disorder, panic disorder, obsessive compulsive disorder, tension anxiety and substance abuse are reportedly more prevalent during fall or winter than during spring or summer (Schlager et al, 1993;Harmatz et al, 2000;Kovalenko et al, 2000;de Graaf et al, 2005). The impacts of seasonal variations has also been studied in common non-communicable diseases (NCDs) such as diabetes, cardiovascular diseases (CVDs), cancer and rheumatic diseases (Hawley et al, 2001;Øyane et al, 2010;Ernst, 2012). Numerous studies have also reported seasonal variations within metabolic syndrome parameters like weight, serum cholesterol level, uric acid, blood pressure, and glucose (Yanovski et al, 2000;Ockene et al, 2004;Liang, 2007;Hayashi et al, 2008;Rintamäki et al, 2008;Alpérovitch et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of seasonality was also reported in connection with the development of some somatic (e.g., acute pancreatitis or tuberculosis [18, 19]) and psychiatric diseases (e.g., seasonal affective disorder [20]). Additionally, seasonal patterns contribute to various health risk behaviours; for instance, seasons influence the amount and frequency of exercise, smoking status [21], and alcohol consumption [22, 23]. As reported by Cho et al [22], heavy episodic drinking behaviour was increased during January and July [22].…”
Section: Introductionmentioning
confidence: 99%